2004
DOI: 10.1103/physrevlett.93.116804
|View full text |Cite
|
Sign up to set email alerts
|

Amphoteric and Controllable Doping of Carbon Nanotubes by Encapsulation of Organic and Organometallic Molecules

Abstract: By using first principles calculations, we show that fine tuning of both p- and n-type doping can be realized on single-wall carbon nanotubes (SWNTs) by tuning the electron affinity or ionization potential of the organic and organometallic molecules encapsulated inside SWNTs. This novel type of SWNT-based material offers great promise for molecular electronics because of its air stability, synthetic simplicity and the abundance of organic and organometallic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 18 publications
3
78
0
Order By: Relevance
“…Empirical and theoretical studies have recently been conducted on the carrier doping of several molecules into SWCNTs. [18,19] The charge transfer between SWCNTs and organic molecules is controlled by the ionization energy or the electron affinity of guest organic molecules and the concentration of molecules, as previously reported by Takenobu et al [14] In this communication, we present the next step towards improving SWCNT device performance, namely, the precise control of carrier density using organic molecules by a solution process. This is the first report of controlled doping in p-type SWCNT-FETs.…”
mentioning
confidence: 84%
“…Empirical and theoretical studies have recently been conducted on the carrier doping of several molecules into SWCNTs. [18,19] The charge transfer between SWCNTs and organic molecules is controlled by the ionization energy or the electron affinity of guest organic molecules and the concentration of molecules, as previously reported by Takenobu et al [14] In this communication, we present the next step towards improving SWCNT device performance, namely, the precise control of carrier density using organic molecules by a solution process. This is the first report of controlled doping in p-type SWCNT-FETs.…”
mentioning
confidence: 84%
“…20 It was found that the carrier type and concentration in CNT can be easily controled by tuning the electron affinity (EA) and ionization potential (IP) of the encapsulated molecules. 20, 21 It is thus very interesting to study the possible electronic structure engineering by organic molecule encapsulation in BNNT.…”
Section: Introductionmentioning
confidence: 99%
“…29a) and F 4 TCNQ@SWCNT (Fig. 29b) samples the flat bands labeled  near the Fermi level of SWCNTs (marked by the dotted line) are related to the lowest unoccupied molecular orbital states of the molecules [356]. These  bands are partially occupied in the molecule-filled SWCNTs.…”
Section: Theoretical Methodsmentioning
confidence: 95%
“…[356] that the filling of the SWCNTs with electrophylic organic molecules (TCNQ and F 4 TCNQ) led to acceptor doping of nanotubes. These calculations were in agreement with earlier reported experimental results [48].…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation